Introduction to Social Network Research: Application of Social Network Analysis in Extension - Anil Kumar Chaudhary; Laura A. Warner (EDIS)
Viewed from a network perspective, we are all part of a network of relationships that is interwoven like a fishing net, providing both opportunities for and constraints on our behavior. Social network analysis (SNA) is a new approach to defining and describing society and its organizations and to assessing the impact of organizational structures. This 4-page fact sheet introduces Extension educators to possible ways to apply SNA in their work to plan and evaluate programs in a more efficient way. Written by Anil Kumar Chaudhary and Laura A. Warner, and published by the UF Department of Agricultural Education and Communication, February 2015.